Isolation and analysis of rereplicated DNA by Rerep-Seq. Issue 10 (2nd April 2020) - Menzel, Johannes; Tatman, Philip; Black, Joshua C
Abstract: Changes in gene copy number contribute to genomic instability, the onset and progression of cancer, developmental abnormalities and adaptive potential. The origins of gene amplifications have remained elusive; however, DNA rereplication has been implicated as a source of gene amplifications. The inability to determine which sequences are rereplicated and under what conditions have made it difficult to determine the validity of the proposed models. Here we present Rerep-Seq, a technique that selectively enriches for rereplicated DNA in preparation for analysis by DNA sequencing that can be applied to any species. We validated Rerep-Seq by simulating DNA rereplication in yeast and human cells. Using Rerep-Seq, we demonstrate that rereplication induced in Saccharomyces cerevisiae by deregulated origin licensing is non-random and defined by broad domains that span multiple replication origins and topological boundaries.